2018
DOI: 10.1038/s41419-018-0552-7
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload promotes mitochondrial fragmentation in mesenchymal stromal cells from myelodysplastic syndrome patients through activation of the AMPK/MFF/Drp1 pathway

Abstract: Iron overload (IO) has been reported to contribute to mesenchymal stromal cell (MSC) damage, but the precise mechanism has yet to be clearly elucidated. In this study, we found that IO increased cell apoptosis and lowered cell viability in MSCs, accompanied by extensive mitochondrial fragmentation and autophagy enhancement. All these effects were reactive oxygen species (ROS) dependent. In MSCs with IO, the ATP concentrations were significantly reduced due to high ROS levels and low electron respiratory chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 52 publications
(57 reference statements)
3
62
0
2
Order By: Relevance
“…reported that iron overload damages MSC through AMPK/MFF/Drp1 pathway in MDS. 27 Thus, further research should investigate the effect of iron overload on the BM microenvironment in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…reported that iron overload damages MSC through AMPK/MFF/Drp1 pathway in MDS. 27 Thus, further research should investigate the effect of iron overload on the BM microenvironment in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Drp1 is activated and causes the fragmentation of mitochondria in neuronal cells ( 95 ). This is linked to iron overload, AMPK activation, MFF ( 96 ), and ubiquitination of A-kinase anchor protein 121 ( 97 ). Conversely, ROS induced mitophagy is suppressed by depleting Drp1 ( 98 ).…”
Section: Mitochondrial Dynamics Plays a Key Role In Immune Cell Metabmentioning
confidence: 99%
“…Repeated blood transfusion could accelerate iron absorption, which results in iron overload in some patients. Iron overload can increase the production of mitochondrial reactive oxygen species (ROS), induce the dysfunction of mesenchymal stem cells [8], promote erythroid apoptosis through regulating HIF-1a/ROS signalling pathway in MDS patients [9], injure the function of MDS-derived mesenchymal stromal cells (MSCs) and promote mitochondrial fragmentation in MSCs from MDS patients [10,11]. In light of this, we could speculate that the deterioration of anaemia in iron overloaded MDS patients may be related to the injury of hematopoietic cell and the abnormality of apoptosis.…”
Section: Introductionmentioning
confidence: 99%